Legal literacy through play: students"™ perceptions of the nomoi board game - Tampubolon, Agustinus; Komalasari, Kokom; Sapriya, Sapriya; Anggraeni, Leni (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2025)
Although legal literacy plays a crucial role in Citizenship Education, legal content often remains abstract and difficult for students to comprehend. This study aims to examine students"™ perceptions of the use of the "Nomoi" board game as a medium for legal literacy learning. A descriptive quantitative approach was employed involving 83 students from a private senior high school in Bandung. The research instrument consisted of a Likert-scale questionnaire that had been tested for validity and reliability. Data were analyzed using descriptive statistics and frequency analysis through SPSS version 27 to identify the dominant trends in students"™ perceptions. The results indicate that most students hold positive perceptions of Nomoi, particularly in terms of engagement, content understanding, and legal awareness. These findings suggest that Nomoi is not merely an educational game but serves as a component of critical citizenship pedagogy that fosters students"™ reflective legal consciousness. As a serious game, Nomoi supports the development of active, collaborative, and meaningful learning. It can be concluded that the integration of a law-based board game into Citizenship Education has significant potential to enhance students"™ legal literacy.